International standards for fetal brain structures based on serial ultrasound measurements from the Fetal Growth Longitudinal Study of the INTERGROWTH-21st Project - Napolitano, R; Molloholli, M; Donadono, V; Ohuma, EO; Wanyonyi, SZ; Kemp, B; Yaqub, MK; Ash, S; Barros, FC; Carvalho, M; Jaffer, YA; Noble, JA; et al. (Wiley, 2020)
OBJECTIVE: To create prescriptive growth standards for five fetal brain structures, measured by ultrasound, from healthy, well-nourished women, at low risk of impaired fetal growth and poor perinatal outcomes, taking part in the Fetal Growth Longitudinal Study (FGLS) of the INTERGROWTH-21st Project.